Plasmid-mediated virulence in Chlamydia - Turman, Breanna J.; Darville, Toni; O'Connell, Catherine M. (Frontiers in Cellular and Infection Microbiology, 2023)
Chlamydia trachomatis infection of ocular conjunctiva can lead to blindness, while infection This is a provisional file, not the final typeset article understanding of plasmid-associated virulence has expanded within the last decade, many questions related to how and to what extent the plasmid influences chlamydial infectivity and inflammation remain, particularly with respect to human infections. Elucidating the answers to these questions could improve our understanding of how chlamydiae augment infection and inflammation to cause disease.